The structure of bird communities in areas revegetated after mining in southern Brazil - Becker, Rafael Gustavo; Paise, Gabriela; Pizo, Marco Aurelio [UNESP] (Soc Brasileira Ornitologia, 2013)
Mined areas undergo physical changes and profound alterations in the structure and composition of the vegetation. Hence, the fauna cannot return to these areas without human intervention, usually through revegetation. In the state of Parana, southern Brazil, we assessed the structure of bird communities (species richness, composition, trophic guilds, and forest dependence) in areas of different ages (5, 10, and 20 years) that were revegetated after mining with a single species of native tree (Mimosa scabrella). These areas were compared with a forest area with no mining influence (control). The areas differed in species richness and species composition. Birds of some foraging guilds (e. g., frugivores) were absent from 10- and 5-year-old areas. The occurrence of forest-dependent birds increased, whereas forest-independent birds decreased with increasing area age. The death of Mimosa scabrella trees between 10 and 20 years after planting reduced vegetation complexity and affected the bird fauna. To avoid such an effect, and to assure the presence of frugivorous birds that are important to restore the vegetation through seed dispersal, we recommend the use of a high diversity of plant species in the initial planting, including plants with fleshy fruits that attract frugivorous birds.
Keywords: Araucaria Forest; foraging guilds; forest dependence; forest restoration; mining areas; restored areas